The Making of Rates for Workmen's Compensation Insurance - Downey, E. H. (Journal of Political Economy, 1917)
Perhaps no phase of workmen's compensation insurance is more interesting, or less familiar, to the layman than the principles and practice of rate-making. If the interested layman be an employer, he has been assured that the rate for his establishment is derived from actual experience, perhaps even that the present rates are the most scientific ever devised by the wit of man;' if an academic inquirer, he has learned of pure premiums, loadings, and multipliers, and of various formulae for the calculation of each; but in neither case has he been able to obtain much information as to the actual processes of rate-making.2 It is hoped, therefore, that a nontechnical analysis of these processes may be of value to that growing body of economic students who concern themselves with social insurance. All insurance rates are made up of two factors: the "pure premium," or actual benefits insured, and the "expense loading,"